2009
DOI: 10.1155/2009/413421
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitive Effect by Acid Extract of Ficus Exasperata Leaves on the Sulphuric Acid Corrosion of Mild Steel

Abstract: Extract ofFicus exasperataleaves was investigated as corrosion inhibitor of mild steel in 1 N H2SO4using conventional weight loss, electrochemical polarizations, electrochemical impedance spectroscopy and scanning electron microscopic studies. The weight loss results showed that the extract ofFicus exasperatais excellent corrosion inhibitor. Electrochemical polarizations data revealed the mixed mode of inhibition. The results of electrochemical impedance spectroscopy shows that the change in the impedance para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…where 'a' and 'b' are intercept and slope, respectively [10]. This isotherm reveals the increased adsorption of the inhibitor on the MS surface with increase in its concentration, and thus the increased protection.…”
Section: Adsorption Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…where 'a' and 'b' are intercept and slope, respectively [10]. This isotherm reveals the increased adsorption of the inhibitor on the MS surface with increase in its concentration, and thus the increased protection.…”
Section: Adsorption Studiesmentioning
confidence: 96%
“…Azoles and N-methyl-p-aminophenol sulphate have been proved as excellent inhibitors of corrosion for mild steel in acid medium [7,8]. Beet root [9] and Ficus Exasperata [10] are also reported to be effective acid corrosion inhibitors. Also acid extracts of Citrus aurantiifolia [11], Nyctanthes arbortristis [12] and Solanum Tuberosum [13] have also been investigated for anticorrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…The use of natural materials as corrosion inhibitors is one of the best options for protecting metals from corrosion attack. These materials have the advantage of being non-toxic, cheap, easily obtainable and environmentally friendly [1][2][3][4][5][6][7][8][9][10]. It has been reported that these natural materials contain abundant phytochemicals (tannins, alkaloids, amino acids, flavonoids, phenols saponins etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of Piper guineense [24,25], Telferiao ccidentalis, Azadirachta indica, Hibiscus sabdariffa [26], Ocimum gratissimum [27], Chamaemelum-mixtum, Nigella sativa L [28], Wrightiatinctoria, Ipomoeatriloba [7] and Lupinousalbus [29] have been investigated for their corrosion inhibition effects on different metals. All the studied extracts proved to be active against the corrosion of the studied metals.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, use of natural plant extracts as eco-friendly and biodegradable corrosion inhibitors has become popular. Literature study shows that green corrosion inhibitor with no environmental hazards is to be discovered or invented 3 .On this note Natural products such as Nyctanthes arbortristis 4 , Acacia trees 5 ,Aloes extract 6 , Terminalia catappa 7 , Cordia Dichotoma 8 , Rauvolfia serpentine 9 , Ginkgo leaves 10 Garlic aqueous extract 11 , Green leafy vegetables 12 and Bauhinia purpurea 13 have been used as inhibitors. Cucurbita maxima belongs to the family cucurbitaceae.…”
Section: Introductionmentioning
confidence: 99%